Phenolic profiles, antioxidant, antiquorum sensing, antibiofilm and enzyme inhibitory activities of selected Acacia species collected from Benin - KOUDORO, YAYA ALAIN (My University, 2022)
Gum arabica is a local commercial nutraceutical and food preservative collected mostly from acacia plants. HPLC-DAD analysis identified gallic acid, syringic acid, ferulic acid, coumarin, rutin and rosmarinic acid in hydroethanol extracts of all three acacia species with ferulic acid being the most abundant component in Acacia ataxacantha (45.25 ± 0.33 mg/g) Acacia sieberiana (130.3 ± 0.65 mg/g) and Acacia nilotica (125.50 ± 0.51 mg/ g). Extracts displayed good antioxidant capacities in β-carotene-linoleic acid, DPPH•, ABTS•+, CUPRAC and metal chelating assays and extracts were more active than the standards used in the DPPH•, ABTS•+ and CUPRAC assays. Extracts inhibited violacein production in Chromobacterium violaceum CV12472 at MIC and sub-MIC concentrations as well as quorum sensing in C. violaceum CV026 under externally supplied acylhomoserine lactone. The extracts showed antimicrobial activity with MIC values ranging from 0.1562 mg/mL to 2.5 mg/mL on Staphylococcus aureus, Enterococcus faecalis, Pseudomonas aeruginosa, Salmonella Typhi, Escherichia coli and Candida albicans with excellent biofilm inhibition at MIC and sub-MIC concentrations especially against E. coli. Extracts showed inhibitions on some enzymes with A. Sieberiana and A. Nilotica having very good anticholinesterase, antidiabetic (α-glucosidase and α-amylase) and antiurease activities. The results indicate the relevance of acacia in food applications.
Keywords: Acacia plants; Phenolic profiles; Antioxidant activity; Quorum-sensing and biofilm inhibition; Enzyme inhibition; Gum arabica